(untitled) (Neo Science Peer Reviewed Journal, 2023)
The article discusses issues of research and knowledge studied by thinkers of antiquity and antiquity, as well as modern scientists. The idea is expressed that students’ research activities are the highest level of a competency-based approach to learning at various levels of education. The author provides facts about the identity of the concepts “research activity”, “research activity” and “research behavior”.